Multi-tag RFID systems. (10th December 2007) - Bolotnyy, Leonid; Robins, Gabriel
Successful object identification is the primary objective of Radio Frequency Identification (RFID) technology. Yet, a recent major study by Wal-Mart has shown that object detection probability can be as low as 66%. We propose the tagging of objects with multiple tags to address the fundamental issue of object detectability. We show that this strategy dramatically improves the efficacy of RFID systems, even in the face of radio noise and other interfering factors. We define different types of multi-tag systems and examine their benefits using analytics, simulations, and experiments with commercial RFID equipment. We investigate the effect of multi-tags on anti-collision algorithms, and develop several techniques that enable multi-tags to enhance RFID security. We suggest new promising applications of multi-tags, ranging from improving patient safety to preventing illegal deforestation. We analyse the economics of multi-tag RFID systems and argue that the benefits of multi-tags will continue to increasingly outweigh their costs in many applications.